Does Political Marketing Strategy Affect Performance of National Political Parties in Lok Sabha Elections ? - Sharma, Pooja; Grover, Abhay (Indian Journal of Marketing, 2021)
India is the largest democratic country in the world. It gives the right to its citizens to vote irrespective of their caste, religion, status, or gender. However, the health of a democracy can be influenced by political marketing. The political parties try to influence the voters, but these parties face various challenges in selecting the correct and best strategy to win the elections. Therefore, the present study was conducted to contribute towards existing literature by examining various political marketing strategies and help the politicians or political parties to understand the marketing dimensions such as voter segmentation, candidate positioning, advertisement and campaigning, political rallies, and opinion polls, which can affect the decision of voters. The study used the data of the last three Lok Sabha elections, that is, 2014, 2009, and 2004 for analysis purposes. Panel least square method was applied to analyze the data. The findings of the study provide better insights to political parties while framing their strategies to influence voters.